SPIRITUALITAS PELAYANAN SANTO DON BOSCO DALAM PENDAMPINGAN KAUM MUDA - Supulangi, Amelisa; Jelahu, Timotius Tote (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2016)
This study aims to find out the youth participation and spiritual contributionof St. Don Bosco for youth assistance in churchâs life in the Parish of St. MikaelTamiang Layang. This research is a descriptive qualitative research with datacollection technique through interview, observation and documentation. Theresult of this study finds out that the youth motivation in church activies is lack.It is caused by internal and external factors. Some internal factors are the lackof awareness, and appreciation of their vocation as the next generation of theChurch. Some external factors are lack of support and motivation from thosearound them. The spirit of service owned by Saint Don Bosco can motivateand assist in mentoring young people to return enthusiastically in performingtheir duties as members of the Church.